Teaching strategies for lecturers and tutors to assist non-English mother tongue tertiary students: Summarising, paraphrasing and vocabulary enrichment - Coullie, J.L. (South African Journal of Higher Education, 2020)
Given the increasingly globalised nature of tertiary education and the growth of English as a second or other language, high numbers of international students studying at English medium tertiary institutions have English as a second (L2) or additional language (EAL). But few efforts may be made to accommodate such students who report that the main difficulty relates to proficiency in English language, and that this results in greater stress and anxiety (Andrade 2006). The key skills of summarising and paraphrasing are reliant upon understanding of concepts and information, in written and oral forms. How can essential content be covered in lectures and tutorials so as to include assistance for non-native speakers of English? I consider a range of pedagogical strategies that can be adopted by university lecturers and tutors to enable EAL students to summarise and paraphrase effectively so as to demonstrate mastery of discipline-specific vocabulary.